A difficult airway approach in a merosin-deficient congenital muscular dystrophy patient: a case report - Jorge Pelicano Paulos; Vanessa Artilheiro; Catarina Cruz; Ana Pinto Carneiro (Brazilian Journal of Anesthesiology, 2023)
Merosin-deficient muscular dystrophy is caused by an autosomal recessive mutation on laminin-..2 gene characterized by severe progressive muscle weakness associated with neuromuscular scoliosis and restrictive lung disease. In this case report, we describe an alternative airway approach performed in a child with anticipated difficult airway and merosin-deficient muscular dystrophy. Significant anesthetic implications may increase the perioperative risk, requiring accurate knowledge to anticipate an adequate management and provide patient-safety strategies.